TURBULENT MIXING PROCESSES IN LABANI CHANNEL, THE MAKASSAR STRAIT - Yuli Naulita (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Study on turbulent mixing processes in Labani Channel, the Makassar Strait, was conducted by using the INSTANT (International Nusantara Stratification And Transport) program dataset, in Juli 2005. The turbulent mixing process was evaluated using Thorpe method, where the overturning eddies were revealed by density inversions in CTD (Conductivity Temperature Depth) profiles. All individual identified-overturn regions was validated by the GK’s test (Galbraith and Kelly test) where at first noise on CTD signals had been removed  by applying wavelet denoising.   A large number of overturn regions with Thorpe scale (LT) less than 0.5 m were detected in the thermocline layer of Makassar Strait. Based on linear relationship between Thorpe and Ozmidov scale, order of magnitude of the turbulent energy kinetic dissipation rate in Labani Channel was estimated about 10-11- 10-5Wkg-1 and density eddy diffusivity Kρ(10-6  – 10-2) m2/s . The strong of turbulen mixing was found at the layer of  NPSW at 150 m depth and NPIW at 300 m depth, indicated by high values of Kρ  (O = 10-3 – 10-2 m2s-1).  It reveals that turbulent mixing has an important role on determining ITF water mass character.  Keywoods: turbulent mixing, wavelet denoising, overturn region, Thorpe method, Labani Channel, Makassar Srait.